THE PERSPECTIVE OF APOSTASY IN MARRIAGE ACCORDING TO ISLAMIC POSITIVE LAW AND THE FIQH OF THE 4 IMAM SCHOOLS - Efita Nurhidayati; Miftakhul Huda (Jurnal Hukum Saraswati (JHS), 2025)
Apostasy before marriage only has an impact on the perpetrator, while apostasy in marriage has an impact on the family. Article 116 letter h of the Compilation of Islamic Law regarding apostasy in marriage is weak, so further discussion is needed. This research uses normative juridical methods with a statutory and conceptual approach, as well as primary, secondary, and tertiary data sources. The results of the study show a difference in perspective between Islamic positive law, namely Article 116 letter h of the Compilation of Islamic Law and Islamic jurisprudence related to apostasy in marriage, especially in terms of tolerance given. In addition, there is a conflict between similar articles and with conflicts with higher provisions